DISEASE PATTERN IN EARTHQUAKE AFFECTED AREAS OF PAKISTAN: DATA FROM KAGHAN VALLEY - Shah, Nasir; Abro, Minhaj Anwar; Abro, Mairaj Anwar; Khan, Asma; Anwar, Fahad; Akhtar, Hina (Journal of Ayub Medical College Abbottabad, 2010)
Background: In 2005 northern parts of Pakistan were hit by an earthquake of magnitude 7.6 on rector scale. Fatima Memorial Hospital established a Primary Health care centre in village of Jared in Kaghan valley. The objective of the study was to find the pattern of different diseases presetting to health centre. Methods: All cases between August 2006 and December 2008 were included from the daily outpatient record of the centre. Data was analyses using SPSS-17. Frequency of different diseases and groups of diseases in different age groups, sexes and time of the year were the main outcome variables. Results: Total number of patients was 22,122 with a mean age of 26±16 years. The number of female patients was 12,634 (57.1%) and males were 9,488 (42.9%). The single most common condition in the study period was viral upper respiratory tract infection (5,042, 23%), followed by Scabies (3,757, 17%), Acid Peptic Disease (3,157, 14.3%), Urinary Tract infection (1,197, 5.4%) and Hypertension (n=933, 4.2%). There was a high number of young patients with urinary tract infection and hypertension. Conclusion: Communicable diseases like viral respiratory tract infection and scabies were the most common infections. Acid peptic disease was the most common non-communicable medical problem. Except eye conditions, all diseases were more common in summer and rainy season. Keywords: Disease pattern, 2005 earthquake, earthquake affected areas, Pakistan